Light trapping in hybrid nanopyramid and nanohole structure silicon solar cell beyond the Lambertian limit - Hong, Lei (2014)
We propose a hybrid nanostructure that comprises nanopyramids and nanoholes for thin film silicon (Si) solar cells. The hybrid structure demonstrates a stronger light trapping ability that is beyond the Lambertian limit. This is achieved with the smaller dimension nanohole structure which effectively reduces shorter wavelength light reflection, and the larger dimension nanopyramid structure which significantly enhances longer wavelength light trapping. An ultimate efficiency of 38.3% is yielded for a 2 μm thick Si cell incorporated with the hybrid structure, which is higher than that achievable corresponding to the Lambertian limit. Moreover, the high ultimate efficiency is retained as the incident angle increases from normal incidence to 50° for TM polarized sunlight. Therefore, the proposed hybrid structure is very promising to enhance the performance of thin film Si solar cells.